Relationship Between Self-Efficacy and Disaster Preparedness Landslide in The Community - Yuni Suharnida Lubis; Anan Rizky; Nadya Ulfa Kesumawardani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The impact of landslides causes a lack of confidence and confidence in the community, so that preparedness and self-efficacy are needed when faced with critical problems such as disasters. This study aims to determine the relationship between self-efficacy and community preparedness in dealing with landslides. Individuals who have high self-efficacy tend to feel confident and confident when preparing for disaster threats, even though the threat of the disaster is a threat. who bears the risk. The sample of this study was 177 respondents and the sampling technique used was purposive sampling. Data collection in the study used a questionnaire, namely preparedness and self-efficacy. Questionnaires were used to analyze demographic characteristics, preparedness, and self-efficacy. The results showed that the majority were average (92.7) adult age male (55.4%). The level of preparedness in the high category is (63.8%) and self-efficacy is (57.1%). Bivariate analysis showed that there was a significant relationship between preparedness and self-efficacy 0.000 (p < 0.05). The strength of the correlation coefficient in the criteria is sufficient (r=0.380). Researchers suggest that the community participation in landslide disaster preparation is supported by good self-efficacy for preparation for landslides in order to reduce disaster risks such as fatalities.